Principles and practice of ophthalmic plastic and reconstructive surgery: Vol. 1 (W. B. Saunders, 1996)
The book has allotted a complete section to systemic diseases and a discussion of systemic perioperative preparation of the surgical patient, including postoperative treatment to enhance and accelerate wound healing. Current and historical surgical advances in eylid reconstriction, ptosis correction, and entropion and ectropion repair are thoroughly presented and documented. A separate section on conjunctival diseases and surgery has been included to highlight their importance and the necessity for alternative techniques in handling conjunctival tissue. The orbital section is voluminous to accommodate the current advanced status of diagnosing and documenting orbital pathology. The anatomic and physiologic distinctions of ethnic ophthalmic patients are also represented in a separate section. In addition, the signifiance of a multidisciplinary approach to the orbit in selected cases is clearly established. The state-of-the-art techniques of socket reconstruction are also presented in a separate section. Ophthalmic plastic surgeons are endeavoring to competitively enter into the arena of aesthenic surgery. The section on cosmetic surgery not only provides the surgical principles but also introduces adjunctive techniques essential to a cosmetic surgical practice: topic home care products, in-office peeling agents, camouflage make-up, and lymphatic drainage massage. New surgical modalities have been introduced: radiosurgery and ultra-pulse laser surgery